17β-estradiol activates SOX6 to balance the anabolism and catabolism via estrogen receptor 2 in chondrocyte: Estradiol balances chondrocyte metabolism - Cao, Ying; Li, Yongji; Yang, Xiangjun; Wang, Hongxu; Liu, Hongpeng (Cellular and Molecular Biology, 2024)
We investigated the influence of 17β-estradiol (17β-E2) on cartilage extracellular matrix (ECM) homeostasis in postmenopausal women. We focused on the roles of estrogen receptors (ESR) and SOX6 in 17β-E2-mediated stimulation of ECM metabolism during chondrocyte (CH) degeneration. We compared the expression of anabolic genes (collagen II and aggrecan) and catabolic genes (MMPs and TIMPs) in IL-1β-induced CH degeneration in vitro, with and without 17β-E2 supplementation. We separately silenced the SOX6, ESR1, and ESR2 genes in CHs to determine their impact on 17β-E2 treatment. Additionally, we used Chromatin immunoprecipitation followed by DNA sequencing (ChIP-seq) and luciferase assays to investigate protein-DNA interactions within ESR2 and SOX6-promoter complexes. After three days of IL-1β treatment, ESR1/2, SOX6, collagen II, aggrecan, and TIMP1/3 were decreased, while MMP3/9/13 were increased. The addition of 17β-E2 partially reversed these effects, but silencing SOX6, ESR1, or ESR2 weakened the protective effects of 17β-E2. Silencing ESR2, but not ESR1, abolished the upregulation of SOX6 induced by 17β-E2. ESR2 was found to bind the SOX6 promoter and regulate SOX6 expression. 17β-E2 upregulates SOX6 through ESR2 mediation, and the synergistic effect of 17β-E2 and ESR2 on SOX6 balances ECM metabolism in CHs.